Answer:
p = - 14
Step-by-step explanation:
Using the rules of exponents
÷
= ![a^{(m-n)}](https://tex.z-dn.net/?f=a%5E%7B%28m-n%29%7D)
= ![a^{mn}](https://tex.z-dn.net/?f=a%5E%7Bmn%7D)
Note 81 = 9² and 729 = 9³
Given
÷ ![(729)^{2-p}](https://tex.z-dn.net/?f=%28729%29%5E%7B2-p%7D)
=
÷ ![(9^{3}) ^{2-p}](https://tex.z-dn.net/?f=%289%5E%7B3%7D%29%20%5E%7B2-p%7D)
=
÷ ![9^{6-3p}](https://tex.z-dn.net/?f=9%5E%7B6-3p%7D)
= ![9^{-8-(6-3p)}](https://tex.z-dn.net/?f=9%5E%7B-8-%286-3p%29%7D)
= ![9^{-8-6+3p}](https://tex.z-dn.net/?f=9%5E%7B-8-6%2B3p%7D)
= ![9^{3p-14}](https://tex.z-dn.net/?f=9%5E%7B3p-14%7D)
Thus
= ![9^{4p}](https://tex.z-dn.net/?f=9%5E%7B4p%7D)
Since bases on both sides are equal then equate the exponents
4p = 3p - 14 ( subtract 3p from both sides )
p = - 14
Answer:
%50
Step-by-step explanation:
%50 male - %50 female
Answer: 871.72 + (0.3926........x 42)
Step-by-step explanation: 23.56 x 37= 871.72
23.56/60= 0.3926................... x 42
Chapter : Algebra
Study : Math in Junior high school
x = 7 + √40
find √x of √x + 1
= √x + 1
= √(7+√40) + 1
in Formula is :
= √7+√40 = √x + √y
= (√7+√40)² = (√x + √y)²
= 7+√40 = x + 2√xy + y
= 7 + √40 = x + y + 2√xy
→ 7 = x + y → y = 7 - x ... Equation 1
→ √40 = 2√xy → √40 = 2.2√10 = 4√10
= xy = 10 ... Equation 2
substitution Equation 1 to 2 :
= xy = 10
= x(7-x) = 10
= 7x - x² = 10
= x² - 7x + 10 = 0
= (x - 5)(x - 2) = 0
= x = 5 or x = 2
Subsitution x = 5 and x = 2, to equation 1
#For x = 5
= y = 7 - x
= y = 7 - (5)
= y = 2
#For x = 2
= y = 7 - x
= y = 7 - (2)
= y = 5
and his x and y was find :
#Equation 1 :
= x = 5 and y = 2
#Equation 2 :
= x = 2 and y = 5
So that :
√7+√40 = √x + √y
= √7+√40 = √2 + √5
And that is answer of question :
= √2 + √5 + 1
<span> He could draw a diagram of a rectangle with dimensions x – 1 and x – 6 and then show the area is equivalent to the sum of x2, –x, –6x, and 6.</span>